2016
DOI: 10.1097/icb.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Implant Removal From Anterior Chamber: Surgical Technique

Abstract: Purpose: To describe a surgical technique for complete and safe dexamethasone intravitreal implant (Ozurdex; Allergan, Inc., Irvine, CA) removal from anterior chamber. Methods: Description of a new surgical technique for Ozurdex removal using a lens injector cartridge. Results: Dexamethasone implant was removed completely from anterior chamber with no damage to corneal endothelium or posterior chamber luxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…× 3 PPV Not mentioned surgical removal: corneal incision and reorientation of implant perpendicular to incision. Then viscoelastic injection distal to implant- implant which caused egression Ruiz-Casas et al [ 28 ]c Male, 64 years old Dislocated lens extracted, vitrectomy, anterior chamber IOL Corneal edema Surgical removal, using a lens injector to capture and remove Ozurdex Vela et al [ 29 ] Female, 65 years old Multiple retinal detachment surgeries, iris-claw IOL No corneal edema Surgical repositioning of implant to VC using 30 g needle. No viscoelastic used Röck et al [ 6 ] Patient 1: Female, 47 years old Patient 2: Male, 76 years old Patient 3: Female, 84 years old Patient 4: Female, 69 years old 1: Noninfectious chronic uveitis, vitrectomy, previous dislocated IOL, scleral fixation IOL 2: pseudoexfoliation syndrome, previous dislocated IOL, vitrectomy, scleral fixation IOL, Irvine-Gass syndrome 3: vitrectomy and scleral fixation IOL, Irvine-Gass syndrome 4: noninfectious chronic uveitis, posterior chamber IOL, partial zonular dehiscence so then vitrectomy and surgical posterior capsulotomy done 1: Corneal edema 2: Corneal decompensation with bullous keratopathy 3: Corneal edema, bullous keratopathy 4: Corneal edema, Descemet’s folds 1: Surgical removal via paracentesis with viscoelastic injection and use of 20 g alligator forceps 2: Surgical removal via paracentesis with viscoelastic injection and use of 20 g alligator forceps 3: DMEK 4: surgical removal Bansal et al [ 30 ] Patient 1: Male, 47 years old Patient 2: Male, 13 years old Patient 3: Male, 15 years old 1: chronic anterior uveitis, post-lensectomy-vitrectomy, aphakia 2: Bechet’s syndrome, post-lensectomy-vitrectomy, aphakia 3: Chronic anterior uveitis, post-lensectomy and vitrectomy, aphakia 1: Corneal edema, Descemet’s folds 2: Corneal edema, elevation of IOP 3: No complications 1: remigrated to vitreous cavity on its own 2: surgical removal 3: remigrated back to vitreous upon supine position Khurana et al [ 31 ] Patient 1: Male, 65 years old Patient 2: Female, 49 years old Patient 3: Male, 61 years old 1: ...…”
Section: Resultsmentioning
confidence: 99%
“…× 3 PPV Not mentioned surgical removal: corneal incision and reorientation of implant perpendicular to incision. Then viscoelastic injection distal to implant- implant which caused egression Ruiz-Casas et al [ 28 ]c Male, 64 years old Dislocated lens extracted, vitrectomy, anterior chamber IOL Corneal edema Surgical removal, using a lens injector to capture and remove Ozurdex Vela et al [ 29 ] Female, 65 years old Multiple retinal detachment surgeries, iris-claw IOL No corneal edema Surgical repositioning of implant to VC using 30 g needle. No viscoelastic used Röck et al [ 6 ] Patient 1: Female, 47 years old Patient 2: Male, 76 years old Patient 3: Female, 84 years old Patient 4: Female, 69 years old 1: Noninfectious chronic uveitis, vitrectomy, previous dislocated IOL, scleral fixation IOL 2: pseudoexfoliation syndrome, previous dislocated IOL, vitrectomy, scleral fixation IOL, Irvine-Gass syndrome 3: vitrectomy and scleral fixation IOL, Irvine-Gass syndrome 4: noninfectious chronic uveitis, posterior chamber IOL, partial zonular dehiscence so then vitrectomy and surgical posterior capsulotomy done 1: Corneal edema 2: Corneal decompensation with bullous keratopathy 3: Corneal edema, bullous keratopathy 4: Corneal edema, Descemet’s folds 1: Surgical removal via paracentesis with viscoelastic injection and use of 20 g alligator forceps 2: Surgical removal via paracentesis with viscoelastic injection and use of 20 g alligator forceps 3: DMEK 4: surgical removal Bansal et al [ 30 ] Patient 1: Male, 47 years old Patient 2: Male, 13 years old Patient 3: Male, 15 years old 1: chronic anterior uveitis, post-lensectomy-vitrectomy, aphakia 2: Bechet’s syndrome, post-lensectomy-vitrectomy, aphakia 3: Chronic anterior uveitis, post-lensectomy and vitrectomy, aphakia 1: Corneal edema, Descemet’s folds 2: Corneal edema, elevation of IOP 3: No complications 1: remigrated to vitreous cavity on its own 2: surgical removal 3: remigrated back to vitreous upon supine position Khurana et al [ 31 ] Patient 1: Male, 65 years old Patient 2: Female, 49 years old Patient 3: Male, 61 years old 1: ...…”
Section: Resultsmentioning
confidence: 99%
“…A repeated Ozurdex injection in patients with previous inferior iridotomy is possible but may require prior suturing of the iridotomy to avoid a repeat migration. Other authors have suggested the use of a lens injector cartridge or vitrectomy instruments and forceps to withdraw the implant from the anterior chamber [3,4]. Although these techniques are successful, the additional costly material to achieve the result may not be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…One may also aspirate the implant into the needle lumen which can also reduce the risk of implant breakage within the eye. 34 A surgical approach, described by Ruiz-casas et al, 35 involves filling the AC with viscoelastic, inserting a viscoelastic-filled lens injector cartridge through a 2.2–2.7 mm corneal incision and using a viscoelastic cannula or lens rotator to gently push the DEX implant into the lens injector and out of the eye. Another method by Lee et al describes introducing a Sinksy hook into the AC through a paracentesis incision to push the implant to the periphery, under the iris and behind the IOL.…”
Section: Discussionmentioning
confidence: 99%